(untitled) (Research, Society and Development, 2022)
Objective: to know the perception of nursing professionals about the practices performed during labor. Methodology: the research is exploratory-descriptive with a qualitative approach. Ten nursing team professionals who work in a public hospital located in the North of Minas Gerais were interviewed. Results: ineffective and harmful practices continue to be used as a routine way in the hospital environment. There was also a lack of scientific knowledge about the use of such practices by nursing technical professionals. Conclusion: harmful and ineffective practices continue to be used, and these are punctuated by several factors, one of which was identified was the physician’s domain, which directly affects the non-autonomy of nursing professionals, because they do not interfere in the decision-making factor of the physician even knowing their contraindications. The role of nurses as an educating agent is evidenced, and should sensitize and mobilize the nursing team for permanent education.